Small Nucleolar RNAs: Insight Into Their Function in Cancer - Liang, Junnan; Wen, Jingyuan; Huang, Zhao; Chen, Xiao-ping; Zhang, Bi-xiang; Chu, Liang (Frontiers in Oncology, 2019)
SnoRNAs are a class of non-coding RNAs, and divided into two classes, C/D box snoRNAs and H/ACA box snoRNAs. The canonical function of C/D box and H/ACA box snoRNAs is 2’-O-ribose methylation and pseudouridylation of ribosomal RNAs, respectively. Emerging evidences demonstrated that snoRNAs were involved in various physiological and pathological cellular processes. Mutations and aberrant expression of snoRNAs were reported in the cell transformation, tumorigenesis and metastasis, indicating that snoRNAs may serve as biomarkers or therapeutic targets of cancer. Hence, it is meaningful to further study the functions and underlying mechanism of snoRNAs. In this review, we summarize the biogenesis and functions of snoRNAs, the association of snoRNAs in different types of cancers and their potential roles in cancer diagnosis and therapy.